Thrombin generation, bleeding and hemostasis in humans: Protocol for a scoping review of the literature. - Joseph R Shaw; Tyler James; Jonathan Douxfils; Yesim Dargaud; Jerrold H Levy; Herm Jan M Brinkman; Risa Shorr; Deborah Siegal; Lana A Castellucci; Peter Gross; Roy Khalife; Christine Sperling; et al. (PLoS ONE)
Introduction Hemostasis and bleeding are difficult to measure. Thrombin generation assays (TGAs) can measure both procoagulant and anticoagulant contributions to coagulation. TGAs might prove useful for the study of bleeding disorders. There has been much progress in TGA methodology over the past two decades, but its clinical significance is uncertain. We will undertake a scoping review of the literature to synthesize available information on the application of TGAs towards the study of bleeding and hemostasis, TGA methodologies being used and to summarize available literature on associations between TGA parameters, bleeding and hemostatic outcomes. Methods and analysis MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials (CENTRAL) will be searched in collaboration with an information specialist. Title/abstract and full-text screening will be carried out independently and in duplicate; eligible study types will include randomized controlled trials, non-randomized studies, systematic reviews, and case series reporting TGA results and bleeding/hemostatic outcomes among humans. Mapping the information identified will be carried out with results presented using qualitative data analytical techniques. Ethics and dissemination This scoping review will use published, publicly available information. Research ethics approval will not be required. We will disseminate our findings using conference presentations, peer-reviewed publications, social media, and engagement with knowledge users. This review will outline knowledge gaps concerning TGAs, better delineate its applicability as a clinically relevant assay for bleeding. and seek to identify ongoing barriers to its widespread adoption in clinical research, and eventually, in the clinical setting. Trail regulations Registration ID with Open Science Framework: osf.io/zp4ge.